THE ROLE OF JOB ROTATION PRACTICES TOWARDS EMPLOYEE PERFORMANCE IN KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) - Tumipa, Vanessa .; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract: Positioning the right employee in the right job would bring the positive impact for the organization. Organization required employee to perform well conducting their job. However, people can not stuck in one job to get multiple skill. They need to adapt to other job and will become an expert in it. This study aims to identify about the role of job rotation practices towards employee performance in Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) and to describe and explore The Role of job Rotation Practices towards Employee Performance in Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL).. This research is using qualitative research method that explores the theories from several journals, articles, books and previous research. The type of this research is descriptive research. Population in this research is the entire employee in KPKNL that ever experienced job rotation. This study found that job rotation bring positive impact for the employee, develop employee performance and there are 3 major factors which is efficiency, productivity, and quality that become the measuring instrument of employee performance. The suggestion for organization, before doing job rotation makeÂ conversation with employee first. For the employee, always learn to get multiple skill.Â Keywords: human resource management, job design, job rotation, employee performance.